Comparison of Elderlys \"Quality of Life\" Living at Homes and in Private or Public Nursing Homes - Ali Hesamzadeh; Sadat Bagher Maddah; Frahnaz Mohammadi; Masoud Fallahi Khoshknab; Mehdi Rahgozar (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: The aim of this study was to compare the quality of life and its dimensions among the elderly people who were living at homes, private or public nursing homes of the city of Tehran. Methods & Materials: This research was a descriptive cross-sectional study. The study population consisted of 96 aged people in three groups of living at homes, in private and public nursing homes in the city of Tehran, whom were selected according to the research criteria. Data were collected using Demographic and LEIPAD quality of life questionnaires. Kolmogorove-smirnov, One way ANOVA, Independent T-test, Kruskal-wallis, and x2 were used for analyzing data. Results: The score of quality of life of the elderly living at theirhomes (65.57) was significantly higher than the score of subjects living in private (50.64) and public nursing homes (51.30). There was a significant difference in the score of dimensions of physical and social functioning and life satisfaction as well as self-care of elderly people living at homes and the elderly living in private and public nursing homes (P<0.05). There was no significant difference between the "quality of life" score of male and female elderly in all three groups of the research. Conclusion: The elderly people living at homes have a better quality of life in comparison with their peers living in private and public nursing homes in the city of Tehran.